Protestant legacies in nordic law: the early modern period - Rasmussen, Tarald; Sunde, Jørn Øyrehagen (Brill | Schöningh, 2023)
The overarching goal of the book is to examine the relations between Lutheran majority traditions and the development of secular law in the Nordic region in the early modern period, from the 16th to the 18th century. The early modern Nordic region included the kingdoms of Denmark/Norway and Sweden – with the Finnish diocese Åbo as part of the Swedish realm. Both kingdoms were consolidated as Lutheran countries after the reformation. While this change occurred in a determined and radical way in Denmark, in Sweden the transformation was more hesitant. Due to its mixed Protestant (Lutheran/Calvinist) and RomanCatholic heritage, case studies dealing with Germany off er interesting comparative perspectives. The authors are experts in church history and legal history from Germany, Belgium, Denmark, Sweden, Finland, and Norway.